2022
DOI: 10.1021/acs.macromol.2c02215
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Mechanical Properties in Linear UHMWPE Using a Heterogeneous Catalytic System

Abstract: Several homogeneous postmetallocene complexes are known to produce weakly entangled ultrahigh-molecular-weight polyethylene (disentangled UHMWPE) under controlled polymerization conditions leading to ultimate mechanical properties. Major challenges in using a homogeneous catalyst system exist such as reactor fouling and uncontrolled polymer morphology, which could be addressed by heterogenization of the single-site complex. In such a scenario, a heterogeneous catalytic system that can synthesize ultrahigh-mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 47 publications
(181 reference statements)
2
25
0
Order By: Relevance
“…With an increase in the polymerization time, the synthesized polymers show a shift in the crossover point (where G′ = G′′ ) to lower frequencies (Table S1, runs 1–2), which is indicative of an increase in the tube renewal time with increasing molecular weight. These observations are in agreement with the previously reported findings using the same catalyst and catalytic systems . The employed catalyst has been shown to exclusively produce linear chains (without the presence of branches), thus allowing application of Mead’s model to correlate the viscoelastic function with the M w .…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…With an increase in the polymerization time, the synthesized polymers show a shift in the crossover point (where G′ = G′′ ) to lower frequencies (Table S1, runs 1–2), which is indicative of an increase in the tube renewal time with increasing molecular weight. These observations are in agreement with the previously reported findings using the same catalyst and catalytic systems . The employed catalyst has been shown to exclusively produce linear chains (without the presence of branches), thus allowing application of Mead’s model to correlate the viscoelastic function with the M w .…”
Section: Resultssupporting
confidence: 91%
“…In a series of publications, it is shown that the low-entangled UHMWPEs synthesized using homogeneous ,, and heterogeneous catalyst systems can be solid-state processed in an eco-friendly way without using any solvent to uniaxially and biaxially oriented objects that have unprecedented high mechanical properties. Systematic solid-state processing was performed using the literature-reported protocol , (with modification wherever necessary) under uniform processing conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In UHMWPE, the low-entangled state allows the fusion of the polymer particles and translation of the macroscopic force (experienced during the uniaxial as well as biaxial stretching) to the macromolecular length scale of the chains. [7,26] The nascent polymer powder is compressed at 130 °C, rolled at 145 °C, and consequently stretched three times to achieve high draw ratios. During the rolling (or calendaring) process the sample changed into a transparent tape suggestive of the sintering during rolling below-melting point (T peak = 158.3 °C and T onset = 148.9 °C).…”
Section: Processing and Mechanical Propertiesmentioning
confidence: 99%